2007
DOI: 10.1137/070682654
|View full text |Cite
|
Sign up to set email alerts
|

When Shil'nikov Meets Hopf in Excitable Systems

Abstract: Abstract. This paper considers a hierarchy of mathematical models of excitable media in one spatial dimension, specifically the FitzHugh-Nagumo equation and several models of the dynamics of intracellular calcium. A common feature of the models is that they support solitary traveling pulse solutions which lie on a characteristic C-shaped curve of wave speed versus parameter. This C lies to the left of a Ushaped locus of Hopf bifurcations that corresponds to the onset of small-amplitude linear waves. The centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
111
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(126 citation statements)
references
References 35 publications
(49 reference statements)
6
111
0
Order By: Relevance
“…EP1t-points have also been seen in a three-dimensional model motivated by studies of semiconductor lasers with optical reinjection [20]. In this case, folds of a single curve of homoclinic orbits again accumulate on a pair of EP1t-points, in a manner similar to that seen in the nine-dimensional calcium model in [4]. The theoretical study of EP1t-points presented here is motivated by our desire to explain the observed folding and accumulation of homoclinic bifurcation curves in these and other systems.…”
Section: Ep1tmentioning
confidence: 64%
See 4 more Smart Citations
“…EP1t-points have also been seen in a three-dimensional model motivated by studies of semiconductor lasers with optical reinjection [20]. In this case, folds of a single curve of homoclinic orbits again accumulate on a pair of EP1t-points, in a manner similar to that seen in the nine-dimensional calcium model in [4]. The theoretical study of EP1t-points presented here is motivated by our desire to explain the observed folding and accumulation of homoclinic bifurcation curves in these and other systems.…”
Section: Ep1tmentioning
confidence: 64%
“…and the values of all constants used in the numerical computations using these equations are given in the Appendix. As described in [4], a branch of E-homoclinic bifurcations is seen to fold many times (in a 'homoclinic snake') for s ≈ 6.7 and p varying between about 1.88 and 2.63. Figure 8.6 shows various parts of the bifurcation diagram and some representative phase portraits for this phenomenon.…”
Section: 2mentioning
confidence: 83%
See 3 more Smart Citations